THE EVOLVING PHARMACOTHERAPEUTIC LANDSCAPE FOR THE TREATMENT OF SICKLE CELL DISEASE - Samir Ballas (Mediterranean Journal of Hematology and Infectious Diseases)
Sickle cell disease (SCD) is an extremely heterogeneous disease that has been associated with global morbidity and early mortality. More effective and inexpensive therapiesare needed. During the last five years the landscape of the pharmacotherapy of SCD has changed dramatically. Currently, there are at least 50 drugs that have been used or under consideration to use for the treatment of SCD. These fall into 3 categories: the first category includes the three drugs (Hydroxyurea, L-Glutamine and Crizanlizumab tmca) that have been approved by the United States Food and Drug Administration (FDA) based on successful clinical trials. The second category includes 22 drugs that failed, discontinued or terminated for now and the third category includes 25 drugs that are actively being considered for the treatment of SCD. New therapies targeting multiple pathways in its complex pathophysiology have been achieved or are under continued investigation. The emerging trend seems to be the use of multimodal drugs (i.e. drugs that have different mechanisms of action) to treat SCD similar to the use of multiple chemotherapeutic agents to treat cancer.